Open Prostatectomy Versus Transurethral Resection of the Prostate, Where Are We Standing in the New Era? A Randomized Controlled Trial - Simforoosh, Nasser; Abdi, Hamidreza; Kashi, Amir Hossein; Zare, Samad; Tabibi, Ali; Danesh, Abdolkarim; Basiri, Abbas; Ziaee, Seyed Amir Mohsen (Urology Journal, 2010)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Purpose: To compare peri-operative and short-term complications of open transvesical prostatectomy (OP) as well as its functional outcomes with transurethral resection of the prostate (TURP) in management of benign prostatic hyperplasia with prostates sized 30 to 70 g. Materials and Methods: Hundred patients who were candidate for the prostate surgery with prostates between 30 to 70 g randomly underwent OP or TURP. Secondary endpoints included international prostate symptom score, residual urine volume, surgical complications, and patients’ quality of life. Patients were followed up for 6 to 12 months after the operation. Results: Fifty-one and 49 patients underwent OP and TURP, respectively. Median (interquartile range) of peak flow rate improvement was 11.1 (7.6 to 14.2) and 8.0 (2.2 to 12.6) in OP and TURP groups, respectively (P = .02). International prostate symptom score improvement did not reveal statistically significant difference between treatment groups. Re-operation due to residual prostate lobe, urethral stricture, and urinary retention was performed in 8 patients in TURP group versus no patient in OP group (P = .006). Dysuria was more frequent in patients that underwent TURP (P < .001). Hospitalization duration was slightly longer in patients that underwent OP (P = .04). Patients’ quality of life was better in the OP group (P = .04). Conclusion: Open transvesical prostatectomy is an acceptable operation for the prostates sized 30 to 70 g. Higher peak flow rate improvement, better quality of life, less frequent dysuria, less need to re-operation, and its ease of learning make open prostatectomy a suitable option to be discussed in patients parallel to TURP.